Relationship between physical activity and socio economic status among preschool children during school hour - Fauzi, Norfazliyn (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Physical activity should be a normal part of daily living habits for young people. Throughout the lifespan, physical activity plays a key part in children physical, social and mental developments. Physical inactivity has been associated with increased of risk factors and can contribute to non-communicable disease such as cardiovascular disease and diabetes mellitus and can become major consequences prevalence of overweight or obesity in children. Physical activity can reduces morbidity and mortality from many of the leading causes of ill health. Physical activity can be influenced by the Socio economic status of the family. Socio economic status should be identified from a young age as a physical activity should be encouraged in children and adolescence. Hence, this study aims to determine the relationship between physical activity and Socio economic status among preschool children aged from 4 to 6 years old during school hour. 30 healthy subjects were recruited in this study. Accelerometers were used to measured physical activity while parental Socio economic status questionnaires were used to determine the Socio economic status of parents or guardian. Based on Pearson correlations, total steps and body mass index (BMI) of subjects were significant with p< 0.02, r=0.538. Family size and total steps shows no significant correlation with (p>0.01, r=-0.282). While socioeconomic status found and educational level have no significant with total steps counts with 0.803 and 0.656 respectively. Thus, as a conclusion, this study found that Socio economic status and physical activity were not interrelated.